Detoxification of Gadung Tuber (Dioscorea Hispida denst) by Heating and Acidification in Flour Processing - Harijono, Harijono; Martati, Erryana; Syafi'i, Imam (Jurnal Teknologi Pertanian, 2009)
Gadung (Dioscorea hispida dennst) is a starchy tuber that contains poisoneous compounds, which is cyanide compound.  Therefore its diversification products are limited.  Only crispy fried chip of gadung product is found in the market.  Proper processing should be developed to eliminate the poisoneous compounds and to produce gadung flour which has many applications.  The aim of this research was to find out an optimum pH and duration of heating to eliminate poisoneous compounds in fresh gadung in flour making process.  It was suggested that heating and ph adjustment could activate endogenous enzymes that responsible for hydrolysis of cyanide compounds into free cyanide.  This research used Randomized Block Design with 2 factors.  The first factor was pH (4; 4.5; and 5), and the second factors was incubation time at 450C for 1, 3, and 5 hours.The result showed that incubation time and pH gave significant effect (α = 0.05) on gadung flour.  Incubation time gave significant effect on moisture content, cyanide content, flour yield, sugar total content, hygroscopicity, and ash content.  Meanwhile, pH value gave significant effect on cyanide and fiber content.  Interaction of the two treatments gave significant differences effect on cyanide content.  The best treatment based on physico-chemical parameter of gadung flour was 5 hours of incubation and pH 5.  It had flour characteristics as follows: 11.26% of moisture content; 19.95 ppm of  cyanide content; 67.2% of starch content; 5.35% of sugar total content; 1.85% of fiber content; 3.66% of ash content; 2.59% of hygroscopicity; 9.9% of yield, and 74.91% of brightness valueKeywords: yams flour, cyanide acid, endogenous enzyme